2005
DOI: 10.1074/jbc.m506441200
|View full text |Cite
|
Sign up to set email alerts
|

Ryanodine Receptor Type 1 (RyR1) Mutations C4958S and C4961S Reveal Excitation-coupled Calcium Entry (ECCE) Is Independent of Sarcoplasmic Reticulum Store Depletion

Abstract: Bi-directional signaling between ryanodine receptor type 1 (RyR1) and dihydropyridine receptor (DHPR) in skeletal muscle serves as a prominent example of conformational coupling. Evidence for a physiological mechanism that upon depolarization of myotubes tightly couples three calcium channels, DHPR, RyR1, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
68
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 69 publications
7
68
0
Order By: Relevance
“…ECCE is not sensitive to Ca 2ϩ store depletion but is activated by membrane depolarization and is sensitive to RyR1 conformation and mutations (39,40). Furthermore, they have presented preliminary evidence that dantrolene also affects ECCE, but not TG-induced SOCE, thereby discriminating between the two processes (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ECCE is not sensitive to Ca 2ϩ store depletion but is activated by membrane depolarization and is sensitive to RyR1 conformation and mutations (39,40). Furthermore, they have presented preliminary evidence that dantrolene also affects ECCE, but not TG-induced SOCE, thereby discriminating between the two processes (41).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies from Pessah and co-workers (39,40) have demonstrated a process of excitation-coupled Ca 2ϩ entry (ECCE) experimentally distinct from SOCE in cultured myotubes. ECCE is not sensitive to Ca 2ϩ store depletion but is activated by membrane depolarization and is sensitive to RyR1 conformation and mutations (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Depolarization-dependent Ca 2+ entry is influenced by expression of various constituents of the EC coupling apparatus including the α 1S and β 1a subunits of Ca V 1.1, 4,5,10 RyR1, 4,5,9-11 JP-45, 19 and calsequestrin1. 19 In the present work, we present the first example of modulation of this mysterious mode of Ca 2+ influx into skeletal muscle by dynamically-regulated cell signaling molecules (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Of these functions, the fundamental abilities of Ca V 1.1 to engage EC coupling by gating the type 1 ryanodine receptor (RyR1) and to conduct L-type current are well-documented. 6 However, the specific route of Ca 2+ permeation for depolarizationdependent entry remains a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation